Pro-Con Debate: 1- vs 2-Hour Fast for Clear Liquids Before Anesthesia in Children. (16th August 2021) - Disma, Nicola; Frykholm, Peter; Cook-Sather, Scott D.; Lerman, Jerrold
Abstract : Perioperative fasting guidelines are designed to minimize the risk of pulmonary aspiration of gastrointestinal contents. The current recommendations from the American Society of Anesthesiologists (ASA) and the European Society of Anaesthesiology and Intensive Care (ESAIC) are for a minimum 2-hour fast after ingestion of clear liquids before general anesthesia, regional anesthesia, or procedural sedation and analgesia. Nonetheless, in children, fasting guidelines also have consequences as regards to child and parent satisfaction, hemodynamic stability, the ability to achieve vascular access, and perioperative energy balance. Despite the fact that current guidelines recommend a relatively short fasting time for clear fluids of 2 hours, the actual duration of fasting time can be significantly longer. This may be the result of deficiencies in communication regarding the duration of the ongoing fasting interval as the schedule changes in a busy operating room as well as to poor parent and patient adherence to the 2-hour guidelines. Prolonged fasting can result in children arriving in the operating room for an elective procedure being thirsty, hungry, and generally in an uncomfortable state. Furthermore, prolonged fasting may adversely affect hemodynamic stability and can result in parental dissatisfaction with the perioperative experience. In this PRO and CON presentation, the authors debate the premise that reducing the nominal minimum fasting time from 2 hours to 1 hour can reduce the incidence of prolonged fasting and provide significant benefits to children, with no increased risks.